Analysis of factors influencing pregnant women's perceptions of Covid-19 vaccination based on the health belief model theory - Sudarmiati, Sari; Rejeki, Sri; Putri, Annissa Septianpita (Science Midwifery, 2024)
The number of pregnant women receiving COVID-19 vaccination in Semarang City has not yet met the government's target. Acceptance of this vaccination is influenced by individual beliefs and perceptions, which can be analyzed using the Health Belief Model theory. This model involves components such as perceptions of vulnerability, severity, benefits, barriers, and triggers for action, including support from health workers and family. This study aims to identify factors that influence pregnant women's perceptions of COVID-19 vaccination. The research design used was a descriptive survey with data collection through a questionnaire that measured various factors related to acceptance of complete COVID-19 vaccination. Samples were taken using a total sampling technique with a total of 159 pregnant women. Data were analyzed using multivariate analysis. The results showed that of the six characteristics of pregnant women, education level had the greatest influence on perceptions of vulnerability, barriers to vaccination, and support from health workers and family. Parity had the most significant influence on perceptions of COVID-19 disease severity, while age had a significant effect on perceptions of vaccination benefits. This study is expected to provide benefits for pregnant women and health workers, especially in improving health education and helping individuals make informed decisions regarding their well-being.